High morphological plasticity and global geographical distribution of the Pacific broad tapeworm Adenocephalus pacificus (syn. Diphyllobothrium pacificum): molecular and morphological survey - Hernández-Orts, Jesús Servando; Scholz, Tomáš; Brabec, Jan; Kuzmina, Tetiana; Kuchta, Roman (Acta tropica, 2015)
The most important causative agent of human diphyllobothriosis in South America, Diphyllobothrium pacificum, is transferred to the original genus Adenocephalus Nybelin, 1931; revised and redescribed on the basis of the evaluation of an extensive material collected mainly from northern fur seal, Callorhinus ursinus, from St. Paul Island, Alaska. Detailed analysis of morphological and morphometrical data shows a high variability in most of the characteristics traditionally used in diagnosis of diphyllobothriid tapeworms. Phylogenetic analyses based on newly characterised sequences of mitochondrial cytochrome c oxidase subunit 1 and nuclear large subunit ribosomal RNA genes consistently reveal Adenocephalus pacificus as a sister lineage to the clade formed of the remaining Diphyllobothrium species and other genera (Digramma, Diplogonoporus, Ligula). Despite the generally similar morphology, A. pacificus can be differentiated from the closely related taxa in the presence of transverse papilla-like tegumental protuberances distributed anteriorly, separated by narrow semicircular grooves on the ventral surface of proglottids between their anterior margin and the anterior edge of the male gonopore, and relatively small eggs. A. pacificus displays a relatively low host specificity (found in 9 of 16 otariids, and in accidental hosts such as man, dog and jackal, the latter representing a new host) and a uniquely wide geographical distribution on both hemispheres. In addition, suitability of morphological criteria used in diagnostics of diphyllobothriid cestodes is discussed.
Keywords: Cestoda; velké ribozomální podjednotky; Diphyllobothriidea; Fur Seals; Diphyllobothriosis; lachtani rodu Arctocephalus a Callorhinus; fylogeneze; Biogeography; cox1; Phylogeny; Helminth; difylobotriáza; Aljaška; respirační komplex IV; Ribosome Subunits, Large; Pseudophyllidea; průzkumy a dotazníky; Electron Transport Complex IV; lsrDNA; Diphyllobothriasis; Animals; Alaska; Microscopy, Electron, Scanning; Seals; zvířata; Surveys and Questionnaires; mikroskopie elektronová rastrovací; Diphyllobothrium